Crystal structure of levalbuterol hydrochloride polymorph A (Xopenex), C13H22NO3Cl. Issue 2 (20th May 2015) - Kaduk, James A.; Zhong, Kai; Blanton, Thomas N.; Gates, Stacy
<x content-type="archive" xml:space="preserve">Abstract</x> The crystal structure of levalbuterol hydrochloride polymorph A has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Levalbuterol hydrochloride polymorph A crystallizes in space group P21 (#4) with a = 8.499 352(15), b = 6.511 726(13), c = 13.182 256(25) Å, β = 102.1157(2)°, V = 713.327(2) Å3, and Z = 2. The most prominent feature of the structure is the two different sorts of hydrogen bonds. Both of the ammonium hydrogens and O17–H40 act as donors to Cl18. The graph sets are C1, 2(4) and C1, 2(7). The result is a zig-zag chain parallel to the b-axis. The two hydroxy groups at the phenyl end of the molecule form another set of chains, both with graph set C1, 1(6), also resulting in a chain parallel to the b-axis. The bulk of the molecule connects these chains in the (101) plane to form a three-dimensional network. The powder pattern is included in the Powder Diffraction File™ as entry 00-064-1494.